Daytime Sleepiness and Sleep Quality among Undergraduate Medical Students in Sialkot, Pakistan - Noreen Maqbool Bokhari; Mubashir Zafar (Dr. Sulaiman Al Habib Medical Journal, 2020)
Background/Objective: Daytime sleepiness and poor sleep quality are common among medical students, and are expected to affect their academic performance. The common problems are duration of sleep, delayed onset of sleep, and daytime sleepiness. The objective of this study is to determine the prevalence of daytime sleepiness and sleep quality and associated risk factors among medical students in a medical college in Sialkot, Pakistan. Methods: In this cross-sectional study, 154 medical students were selected through stratified random sampling techniques. Pittsburgh Sleep Quality Index (PSQI) was used to assess the sleep pattern and Epworth Sleepiness Scale (ESS) was used to measure daytime sleepiness. The association of sleep quality and daytime sleepiness and the risk factors were determined through regression analysis. Results: The results showed that students who suffered from poor sleep quality was 64%; abnormal sleep latency was 51%, narcoleptic 43.2%, and sleep disturbance 31%. In the multivariate analysis after adjustment of covariates, in terms of sleep habits, females and second academic year students were more than two times likely to have a sleep disorder [Odds Ratio (OR) = 2.33; 95% Confidence Interval (CI), 1.66–2.91 and OR = 2.33; 95% CI, 2.74–7.34, respectively]. Regarding narcolepsy, female participants (OR = 2.03; 95% CI, 1.24–16.7), stress during examination (OR = 1.90; 95% CI, 1.07–47.05), poor sleep after physical activity (OR = 1.76; 95% CI, 1.10–30.00), and second academic year students (OR = 2.07; 95% CI, 1.85–2.54) were two times more at risk of severe narcolepsy. Conclusion: The majority of students suffered from poor sleep quality and daytime sleepiness. Female sex and academic years were the major predictors of poor sleep quality and daytime sleepiness. There is a need for awareness and counseling among students to help reduce the burden of sleep disorder.